1994
DOI: 10.1111/j.1348-0421.1994.tb01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine Hydrochloride and Acetylsalicylate Kill Bacteria by Disrupting the Bacterial Membrane Potential in Different Ways

Abstract: Lidocaine hydrochloride (LH), a local anesthetic, and acetylsalicylate (AcSAL), show antibacterial activity for both gram-negative and gram-positive bacteria. Kinetic studies indicated that antibacterial activity of LH was different from that of AcSAL. A subinhibitory concentration of LH and AcSAL enhanced the sensitivity of Escherichia coli, Salmonella typhimurium, and Pseudomonas aeruginosa to novobiocin and nalidixic acid. The synergistic effect of AcSAL with novobiocin and nalidixic acid was higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 29 publications
1
14
0
2
Order By: Relevance
“…Other compounds had only limited effects, if any, on the susceptibility levels of PAO1 to these antibiotics. Interestingly, tetracain demonstrated strong synergism with novobiocin, a property already noted for some other local anesthetics (22,37). These results confirm that efficient permeabilizers may produce sufficient damage to the outer membrane bilayer to increase strongly the penetration of lipophilic antibiotics via the LPS uptake route (36,53).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Other compounds had only limited effects, if any, on the susceptibility levels of PAO1 to these antibiotics. Interestingly, tetracain demonstrated strong synergism with novobiocin, a property already noted for some other local anesthetics (22,37). These results confirm that efficient permeabilizers may produce sufficient damage to the outer membrane bilayer to increase strongly the penetration of lipophilic antibiotics via the LPS uptake route (36,53).…”
supporting
confidence: 68%
“…The following agents, some of which have been suspected to permeabilize the outer membrane of gram-negative bacteria, were screened for potential cell surface activity in the absence of competing cations: acetylsalicylate (18,37), amiloride (20), ascorbate (18), azithromycin (9), ceftazidime, cetrimide (18), ciprofloxacin, crystal violet, erythromycin, fosfomycin, imipenem, nalidixic acid, p-aminobenzoate (43), pefloxacin, rifabutin, rifampin, sodium azide, tetracycline, trimethoprim, and vancomycin (8). None of these agents exhibited a noticeable action on the permeability of PAO1 cells to testosterone when assayed at 100 M (final concentration) (P Յ 130 nm s Ϫ1 ).…”
mentioning
confidence: 99%
“…It has been reported that lidocaine has rapidly inhibited the generation of membrane potential in the inverted membrane vesicles of bacteria. It has been suggested that inhibition of membrane potential might contribute to the killing of bacteria, and that outer membrane changes might facilitate access to the inner membrane as a major target of killing (Garlid and Nakashima, 1983;Ohsuka et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…They have been shown to bind to the membranes of bacteria, alter their structure and fluidity (20), and disrupt membrane potential (18). Procaine, like ethanol, has been shown to inhibit signal peptide cleavage (12).…”
Section: Effect Of Cell Wall Inhibitors On Pertussis Toxin Secretionmentioning
confidence: 99%